Bioaktif Belimbing Wuluh (Averhoa bilimbi (Linn.)) Terhadap Kadar Formalin Dalam Tahu - Rinza Rahmawati Samsudin (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2018)
This study aims to determine the influence of the juice of belimbing wuluh to the content of formalin in tofu and know the concentration of belimbing wuluh feeling is most effective in reducing the content of formalin in tofu. This study used a complete randomized design. The sample of this study was 30 tofu containing  formalin which was divided into 6 groups. The weight of each sample is 15 grams.The data of the research were analyzed by using anova test with 95% confidence level, then Duncan test with 95% confidence level. From the result of this research can be concluded that there is influence to formalin content in tofu. The content of formaldehyde in the highest to the lowest yields was found in soaking the belimbing wuluh with the concentrations is the group without treatment (8269.40 mg / Kg), 0% (1434.20 mg / Kg), 100% (762.00mg / Kg), 25% (573.80 mg / Kg), 75% (442.20 mg / kg), and 50% (162.00 mg / kg). The highest decrease in formaldehyde content in tofu by 98.40% occurred in the group K3 with the most effective 50% concentration to decrease the formalin content in tofu. Keyword : belimbing wuluh, tofu, formalin